2013
DOI: 10.1097/igc.0b013e318295fb41
|View full text |Cite
|
Sign up to set email alerts
|

Use of Abdominal Radical Trachelectomy to Treat Cervical Cancer Greater Than 2 cm in Diameter

Abstract: The 5-year survival rate (93.5%) for this case series is equal (or better) to rates reported in the literature for patient treated with radical hysterectomy. Our survival data seem to support the hypothesis that ART is a safe treatment option for patients with invasive cervical cancer lesions of more than 2 cm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
53
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 31 publications
(36 reference statements)
4
53
0
3
Order By: Relevance
“…All of these factors provide future challenges for better preoperative selection of patients and appropriate surgical approaches. If the cervical cancer is greater than 2 cm in diameter, ART might be suitable to obtaining good oncological results [26][27][28]. Additionally, cerclages should be carefully placed, and anti-stenosis tools are highly recommended to reduce the incidence of cervical stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…All of these factors provide future challenges for better preoperative selection of patients and appropriate surgical approaches. If the cervical cancer is greater than 2 cm in diameter, ART might be suitable to obtaining good oncological results [26][27][28]. Additionally, cerclages should be carefully placed, and anti-stenosis tools are highly recommended to reduce the incidence of cervical stenosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another study performed by Wethington et al (12) on 110 patients of stage 1B1, 29 had a tumor size of 2-4 cm; 9 from this group of 29 patients underwent trachelectomy, and after a median follow up of 44 months, there was one recurrence. In a study performed by Lintner et al (13) on 45 patients with FIGO stage 1B1-1B2, all patients with tumor size 2-4 cm had a 5-year survival of 93.5% which is comparable to radical hysterectomy. Most centers include 1B1 tumors with size less than 2 cm only (14).…”
Section: Discussionmentioning
confidence: 99%
“…Of 113 patients who attempted to get pregnant, 67 (59%) were able to conceive (17). Lintner found that the 5 year survival rate was 93.5% and 3 out of 8 patients delivered healthy neonates (18). In a retrospective study done by Lu et al (19), in 25 patients with ear-ly stage cervical cancer treated by laparoscopic RT, there was no intraoperative complications but 3 postoperative complications were observed.…”
Section: Complication Oncologic Safety and Pregnancy Outcome Of Radimentioning
confidence: 99%
“…[3], РАТ можно вы-полнять при IВ1-В2 стадии и размере опухоли более 2 см, при этом частота 5-летней выживаемости составля-ет 93,5%. Безусловно, данная операция, в объем которой входит не только удаление шейки матки и формирование маточно-влагалищного анастомоза, но и удаление пара-метральной клетчатки -выполнение подвздошно-обту-раторной лимфаденэктомии, негативно сказывается на репродуктивном прогнозе у пациенток.…”
unclassified
“…Безусловно, данная операция, в объем которой входит не только удаление шейки матки и формирование маточно-влагалищного анастомоза, но и удаление пара-метральной клетчатки -выполнение подвздошно-обту-раторной лимфаденэктомии, негативно сказывается на репродуктивном прогнозе у пациенток. Так, частота на-ступления беременности при выполнении операции от-крытым доступом не превышает 6,6% по отношению ко всем выполненным процедурам [3]. Несколько большая частота наступления беременностей отмечена в исследо-вании H. Nishio и соавт.…”
unclassified